2004
DOI: 10.7863/jum.2004.23.11.1433
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of 3‐Dimensional Saline Infusion Sonography in Addition to 2‐Dimensional Saline Infusion Sonography in Women With Abnormal Uterine Bleeding

Abstract: Objective. To evaluate the clinical relevance of 3-dimensional saline infusion sonography (3D-SIS) in addition to conventional SIS in women with abnormal uterine bleeding suspected of having intrauterine abnormalities. Methods. All women suspected of having intrauterine abnormalities were eligible. Before 3D-SIS, conventional SIS was performed. The results of these techniques were compared with the "combined method reference standard" (hysteroscopy, endometrial sampling, and clinical followup in cases with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 35 publications
1
15
2
Order By: Relevance
“…This may be one of the reasons why gel instillation is associated with less procedurerelated pain compared with saline infusion. Promising results with three dimensional (3D) SIS in the evaluation of abnormal vaginal bleeding or uterine abnormalities have been published (10,11). Because a stable filling of the uterine cavity is mandatory for 3D-volume acquisition, 3D GIS is expected to allow for an equal or better 3D-image quality, without the necessity for a balloon catheter.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons why gel instillation is associated with less procedurerelated pain compared with saline infusion. Promising results with three dimensional (3D) SIS in the evaluation of abnormal vaginal bleeding or uterine abnormalities have been published (10,11). Because a stable filling of the uterine cavity is mandatory for 3D-volume acquisition, 3D GIS is expected to allow for an equal or better 3D-image quality, without the necessity for a balloon catheter.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity in this study for both 2DSIS and 3DSIS are overall consistent with the reported sensitivity and specificity for SIS in the literature. de Kroon et al 9 in a meta-analysis reported on pooled sensitivity of 95% for all pathology, 86% for polyps, and 87% for myomas and pooled specificity of 88% for all pathology, 81% for polyps, and 92% for myomas. The specificity in our study for endometrial polyps was 64% for 2DSIS and 75% for 3DSIS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have appeared about 3-dimensional sonohysterography with SIS (20,21). A more stable filling of the uterine cavity with gel allows a longer investigation time, which results in better 3-dimensional sonohysterographic images with fewer artifacts and moving tissue elements than with flushing saline.…”
Section: Exalto Gel Instillation Sonohysterography Fertil Steril 2007mentioning
confidence: 98%